Penerapan Teknologi Biopori Untuk Mengurangi Banjir di TPA Kampung Galaxy Kota Bengkulu - Dewi Marliani; Istiana Istiana; Ahmad Walid (Journal of Social Responsibility Projects by Higher Education Forum, 2020)
Environmental problems have become a global problem. The problem of flooding that has hit various cities in Indonesia including Bengkulu City in the galaxy village is an indicator that there has been a decline in environmental quality. With these problems, it is necessary to have socialization about increasing environmental awareness to build a community that cares about the environment through the making of biopore infiltration holes (LRB). LRB is an appropriate technology engineering to overcome the problem of limited land as a water catchment area. The aim of making LRB is to increase public awareness of the environment so that the environment becomes healthy, green, and sustainable. The output target to be achieved through counseling and training is to foster a love for the environment for the young generation as the pillars of the future church regarding the importance of using organic waste into compost and applying the right technology to increase water absorption or soil conservation through making biopore infiltration holes. village of galaxy